On the expansion of the areas of Vespa orientalis and Polistes wattii (Hymenoptera: Vespidae) on the territory of the Republic of Kazakhstan - I. I. Temreshev (Acta Biologica Sibirica, 2018)
The new data received on the distribution of two species of social wasps in the territory of the Republic of Kazakhstan-the eastern, or Vespa orientalis Linnaeus, 1771 (Oriental hornet), and the Polistes wattii Cameron, 1900. Currently in territory of Almaty oblast there is a stable self-reproducing population of the V. orientalis and its range is constantly expanding. On the territory of the Zhambyl oblast, it was previously recorded in the Talas district, but for Shu and Sarysu districts not indicated. In the Kyzylorda oblast, it was previously recorded in the Syrdarya district, for the Zhanakorgan district not specified. In general, it not specified earlier for the Karaganda oblast. Thus, in general, the territory of Kazakhstan is expanding its range. P. wattii in Kazakhstan was observed relatively recently (2012, the villages of Shardara and Asykata in Shardara and Maktaaral districts of the South Kazakhstan oblast). North of the indicated points of South Kazakhstan and in the Kyzylorda and Zhambyl oblasts, it was not previously indicated. Apparently, the species gradually expands its area within the Republic of Kazakhstan. Both species are of practical importance as pests of agriculture and beekeeping, and sanitary and epidemiological and medical - as poisonous animals. In addition, their introduction into new habitats can disrupt the existing ecological balance. Proceeding from, is necessary to monitor further spreading of these wasps within Kazakhstan, and to start working on the issue of measures to limit their numbers taking into account world experience.